1999
DOI: 10.1037/1064-1297.7.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of morphine-induced effects on thermal nociception, mechanoreception, and hind limb flexion in chronic spinal rats.

Abstract: The effect of systemic morphine on 3 behaviors in the same group of chronic spinal rats was examined: the tail-flick (TF) reflex to a noxious thermal stimulus, limb withdrawal (LW) to mechanoreceptor (von Frey hair) stimulation, and hind limb flexion (flexor reflex [FR]) elicited by innocuous electrical stimulation of the toes. Compared with intact rats, the potency of morphine on both the TF and the hind paw (but not the forepaw) LW response was significantly reduced. Morphine's effect on the FR depended on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In regards to analgesic efficacy, these impairments can compromise interpretation of analgesic results, as an animal may be immobilized or unresponsive when tested at these doses. This may be problematic in that high doses of morphine (> 3 mg/kg) are required to suppress reflexive assays of pain measurement [ 49 - 51 ] and are relatively higher as compared to doses in humans (< 0.15 mg/kg) that are effective for controlling clinical pain [ 52 ]. While it is possible that a differential expression rate of opioid receptors between species may explain this discrepancy in dose, the non-analgesic effects including sedation and suppression of reflex responses cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to analgesic efficacy, these impairments can compromise interpretation of analgesic results, as an animal may be immobilized or unresponsive when tested at these doses. This may be problematic in that high doses of morphine (> 3 mg/kg) are required to suppress reflexive assays of pain measurement [ 49 - 51 ] and are relatively higher as compared to doses in humans (< 0.15 mg/kg) that are effective for controlling clinical pain [ 52 ]. While it is possible that a differential expression rate of opioid receptors between species may explain this discrepancy in dose, the non-analgesic effects including sedation and suppression of reflex responses cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that endogenous opioids such as enkephalins and dynorphins play a crucial role in pain control at both spinal and supraspinal level (Basbaum and Fields, 1984;Faull and Villiger, 1987;Stevens and Seybold, 1995;Coggeshall and Carlton, 1997). A rich vein of studies have demonstrated that the FR is strongly influenced by the opiates and opioids in animals (Catley et al, 1984;Woolf and Wall, 1986a;Clarke and Ford, 1987;Hori and Watanabe, 1987;Gamble and Milne, 1990;Hao et al, 1990;Wiesenfeld-Hallin et al, 1991;Xu and Wiesenfeld-Hallin, 1991;Carstens and Ansley, 1993;Luo et al, 1994;Schomburg and Steffens, 1995;Tokuyama et al, 1998;Advokat and Duke, 1999;Hu et al, 1999;Clarke and Ward, 2000;Gozariu et al, 2000;Schomburg et al, 2001;Jenkins et al, 2004).…”
Section: Opioids-morphine Naloxone and Othersmentioning
confidence: 99%